Probe Array from BeCu Metal Sheet Using Heat and Fusing Currents - Kim, Sangwon; Cho, Chanseob; Kim, Bonghwan (International Journal of Engineering and Technology, 2018)
A probe array fabricated from a beryllium-copper metal sheet was developed in order to produce cost-effective microelectromechanical system (MEMS) probe cards. The probe array is fabricated via a simple, inexpensive process in which a heat current is used for annealing and a fusing current from a DC power supply is used for cutting the metal sheet. The stress relaxation time was 7 min during the application of a 4 A heat current, and the fusing current was 20 A. The contact force was approximately 1 gram force at a deflection of 100 Î¼m, and the contact resistance from the tip of the probe to the end of the probe beam was 1.9 â„¦. The probe array is suitable for use in probe cards, test sockets, and various types of manufacturing equipment.Â Â